Foreword - Rian Venter (Acta Theologica)
From text: The position of theology at a public and secular university has become a contested issue in recent years. In a country like South Africa, with a multi-religious population and a secular constitution, Christian theology should account increasingly for its legitimacy among the other academic disciplines. During a strategic planning process, the Faculty of Theology at the University of the Free State opted intentionally to expand its mission and focus on not only the church as public, but also society and the academy. Initiating and stimulating interdisciplinary conversation on the campus is considered one aspect of such an expansion.